Clearance of cardiovascular medications during hemodialysis. Issue 3 (May 2016) - Tieu, Alvin; Leither, Maxwell; Urquhart, Bradley L.; Weir, Matthew A.
Abstract : Purpose of review: To review the current understanding of hemodialysis-mediated clearance of commonly used cardiovascular medications. Recent findings: Although cardiovascular drug dialyzability is poorly understood, many drug classes appear to include agents with substantially different degrees of dialyzability. Recent data suggest that more readily dialyzable beta-blockers associate with higher short-term mortality in patients initiating these drugs when on hemodialysis. Although this relationship was not observed in a later study with angiotensin-converting enzyme inhibitors of varying dialyzability, studies of this kind are currently limited by pharmacokinetic data that are either incomplete or no longer applicable to modern hemodialysis procedures. Summary: There are substantial deficits in our understanding of cardiovascular medication dialyzability, which relates in large part to advances in the process of hemodialysis that have rendered older studies of dialyzability irrelevant. The importance of cardiovascular disease in patients receiving hemodialysis demands a better understanding of the effect hemodialysis exerts on cardiovascular drug pharmacokinetics.